41 National early warning score (NEWS) evaluation in an ambulance-nurse: one-year experience in portugal. (26th April 2019) - Vasconcelos, P; Oliveira, A; Augusto, T; Ladeira, L; Lourenço, J; Barros, F; Ramos, R
Abstract : Background: Several studies published showed the application of the Early Warning Scores (EWS) in prehospital setting. This article aims to reflect the prehospital emergency nurse´s intervention, acting under pre-established medical protocols, in the clinical evolution of the critically ill patient, through the application of the NEWS2 score. Method: This is a retrospective analysis of cases during one year in an urban ambulance-nurse staffed (SIV-Lisboa), by the application of the NEWS2 in three different moments: at arrival of the team, after the first interventions and at hospital admission. Results: Between October 1, 2017 and September 30, 2018, SIV-Lisboa assisted 2387 patients, of which 1825 patients were elected to this study. At the arrival of the ambulance team, 36.77% of the patients showed Red Score, 0.55% High Score, 1.32% Medium Score, 60% Low Score and in 1.37% of the cases there were a missing item. At hospital admission, 52.9% of the red scored patients improved to lower scores. Conclusion: The application of NEWS2 by an ambulance-nurse staffed allows to identify the criticity of the patient, optimizing the communication between nurse and doctor, in dispatch center, allowing to evaluate the success of the interventions performed by nurses in the prehospital phase. The analysis of the data concluded that the nursing intervention proved to be effective in stabilizing the critical patient. In the future, it will be interesting to expand the application of this score to all ambulance-nurse staffed, making possible a national wide analysis. References: Morgan R, Williams F, Wright M. An early warning scoring system for detecting developing critical illness. Clin Intensive Care . 1997; 8–100. Martín-Rodrigues F, Castro-Villamor MA, Del Pozo Vegas C, Martin Conti JL, Mayo-Iscar A, Delgado Benito JF, Del Brio Ibañez P, Arnillas-Gomez P, Escudero-Quadrillero C, Lopez-Izquierdo R. Analysis of the early warning score to detect critical or high-risk patients in the prehospital setting. Intern Emerg Med 2019 Jan. Shaw J, Fothergill R, Clarck S, Moore F. Can the prehospital National Early Warning Score identify patients most at risk from subsequent deterioration? BMJ 2017. Conflict of interest: None. Funding: None.